Potassium leaching in different soils as a function of irrigation depths - Walter da C. Mendes; José Alves Júnior; Paulo C. R. da Cunha; Anderson R. da Silva; Adão W. P. Evangelista; Derblai Casaroli (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Potassium (K) can be easily lost by the leaching process. The objective of this study was to quantify K leaching in clayey and sandy soils under increasing irrigation depths. The experiment was conducted in 2014, in a protected environment, after extraction of undisturbed soil columns, with diameter of 144 mm and height of 300 mm. The columns were arranged in a randomized complete block in a factorial design with three replicates, corresponding to eight treatments: two soil types and four water depths, equivalent to 50, 100, 150 and 200% of the amount of water necessary to bring the soil moisture to field capacity. Potassium chloride, with 58% of K2O, was used as K source. Water replacement in the columns was performed every three days, for a period of 81 days. After conducting joint analysis of the data according to the factor Time, a second-degree response surface model was fitted and line charts were also used to study the factors Time and Water. After the evaluations, it was found that the higher the applied water depth, the greater the percolated amount of the K+ ion.